196k views
0 votes
Question 6(Multiple Choice Worth 1 points)

(08.05 MC)
The function f(x) = x2 + 6x + 3 is transformed such that g(x) = f(x - 2). Find the vertex of g
(-1,-8)
(-3,-4)
(-1,-6)
(-5-6)​

User Amaters
by
6.4k points

1 Answer

5 votes

Answer:

(-1,-6)

Explanation:

We have the following function:


f(x) = x^(2) + 6x + 3

The following transformation is applied


g(x) = f(x - 2)

So


g(x) = f(x - 2) = (x - 2)^(2) + 6(x - 2) + 3


g(x) = x^(2) - 4x + 4 + 6x - 12 + 3


g(x) = x^(2) + 2x - 5

For a second order function in the format:


g(x) = ax^(2) + bx + c

The vertex is:


V = (x_(v), g(x_(v))

In which


x_(v) = -(b)/(2a)

In this problem


a = 1, b = 2

So


x_(v) = -(2)/(2*1) = -1

Then


g(x_(v)}) = g(-1) = (-1)^(2) +2(-1) - 5 =  -6

So the correct answer is:

(-1,-6)

User Lmcanavals
by
5.3k points